Upholding ethos in education - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
QATAR University held its Annual Research Forum and Exhibition in Doha last week. It was aimed at sharing with the larger community what has been going on in the campus covering live research demonstrations, poster presentations, sharing of graduate experiences as well as international seminars and panel discussions. The two-day event themed Research Transformation through the Fourth Industrial Revolution: Challenges and Social Innovations was well organised.